Designing a mobile broadband wireless access network. - Laroia, R.
In this paper, a new OFDM-based air interface technology for a mobile broadband wireless system is described. The technology leverages the standard Internet protocol (IP) network elements to build the system and deploys a new air interface technology based on OFDMA. Cross-layer optimization played a major role in the design where the choices made in the physical, MAC, and link layers are also driven by the goal of extending the Internet to the wireless space. A major physical layer benefit of this air interface comes from the orthogonality property that the results in the elimination of in-cell interference are averaged and a worst-case interferer does not limit the system performance. The physical layer features not only result in high capacity but also provide very fine granularity of allocating air link resources, which improves the MAC and link-layer efficiency. The MAC and link layer provide contention-free, fast control channels between the RAR and the WTs. These channels are used to ferry a variety of signaling such as assignments of traffic channel, acknowledgements, channel quality, and traffic request reports. This holistic approach allows for a scheduler that could not only achieve high spectral efficiency but also allow for a fine control over QoS attributes such as latency, reliability, and service differentiation.
Keywords: Internet protocol network; QoS; Air interface technology; Air link resources; Channel quality; Cross-layer optimization; In-cell interference; Mobile broadband wireless access network; Orthogonal frequency division multiplexing; Quality of service; Radio access router; Traffic channels; Traffic request reports; Wireless terminals